2014
DOI: 10.1103/physrevc.89.014620
|View full text |Cite|
|
Sign up to set email alerts
|

Relativistic impulse approximation analysis of elastic proton scattering from He isotopes

Abstract: Recent relativistic mean field (RMF) calculations have provided nuclear distributions of some isotopes whose mass numbers are much larger than atomic numbers. For helium isotopes, the RMF calculation seems to be inappropriate because of the small mass numbers; however, applicable results are obtained for 6,8 He nuclei. The author calculates observables of proton elastic scattering from the helium isotopes and discusses relations between observables and nuclear distributions of the isotopes by comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A systematic Bruckner-Hartree-Fock study of the light nuclei was also performed and found to have large sensitivity to the NN potential and the A y observables in [16]. The Eikonal approximation was used on the helium isotopes in [17] while a relativistic impulse approximation study was undertaken in [18] with again limited success. Some researchers have had moderate success by starting with a traditional microscopic gmatrix model but then broadening the target density [19].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic Bruckner-Hartree-Fock study of the light nuclei was also performed and found to have large sensitivity to the NN potential and the A y observables in [16]. The Eikonal approximation was used on the helium isotopes in [17] while a relativistic impulse approximation study was undertaken in [18] with again limited success. Some researchers have had moderate success by starting with a traditional microscopic gmatrix model but then broadening the target density [19].…”
Section: Introductionmentioning
confidence: 99%
“…See Refs. [14][15][16]22] for details. Local forms of the optical potentials have been found to be accurate at high energy for nucleon-nucleus elastic scattering due to the diffractive nature of the scattering.…”
Section: A Relativistic Impulse Approximationsmentioning
confidence: 99%